Quality of Life Among Informal Sector Workers in Relation to Working Hours, Income, and Social Support - Nuraini Nuraini; Tri Niswati Utami (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
The quality of life of informal sector workers is related to their work-life balance, job satisfaction, and health problems. Prevention of work accidents, occupational diseases, and welfare improvement are regulated in the occupational health and safety management system. The purpose of analyzing their quality of life. A cross-sectional design was conducted for this research, from May to August 2025 on online platform drivers. Accidental techniques and establishing inclusion criteria were used to determine the research sample. The instrument used was a questionnaire that had met validity and reliability standards. Multivariate regression was used for data analysis. The results of the study found that their quality of life was related to income, social support, and working hours, stated at a p value <0.001. Of the three variables related to quality of life, working hours/week showed a negative relationship with a B value of -0.231, while the other two variables were positive. The higher the number of hours worked by online platform workers per week, the lower their quality of life. In contrast to income, the t value = 5.576 and p = 0.000 means that income is correlated 5 times with quality of life. High income means their quality of life is 5 times better. Social support was proven to be significantly related to quality of life with a p value of 0.000 and t value of 12.038. Positive social support was associated with 12 times better quality of life for workers Keywords: ISO 45001, Long Working Hours, Platform work, Quality of Life, Total worker health